Quality-of-Life Outcomes Improve with Nipple-Sparing Mastectomy and Breast Reconstruction. Issue 2 (August 2017) - Bailey, Christopher R.; Ogbuagu, Onyebuchi; Baltodano, Pablo A.; Simjee, Usamah F.; Manahan, Michele A.; Cooney, Damon S.; Jacobs, Lisa K.; Tsangaris, Theodore N.; Cooney, Carisa M.; Rosson, Gedge D.
Abstract : Background: Loss of the nipple-areola complex can be psychologically and sexually devastating. Nipple-sparing mastectomy provides robust cosmetic results, but few studies have investigated the quality-of-life outcomes associated with it. Methods: The authors performed an institutional review board–approved retrospective study of 32 patients who underwent nipple-sparing mastectomy with implant-based or autologous reconstruction and 32 control patients who underwent non–nipple-sparing mastectomy with reconstruction matched by reconstruction type and operative period. They then compared premastectomy and postreconstruction responses to the BREAST-Q, a validated and breast reconstruction–specific quality-of-life questionnaire, within and between their study and control populations. Results: The nipple-sparing and non–nipple-sparing mastectomy groups were statistically similar in terms of mean age [49.9 ± 8.5 years (range, 36 to 69 years) and 47.7 ± 10.3 years (range, 26 to 68 years) ( p = 0.29), respectively] and mean body mass index [24.3 ± 3.5 kg/m 2 (range, 17.9 to 33.7 kg/m 2 ) and 25.5 ± 5.4 kg/m 2 (range, 19.2 to 39.2 kg/m 2 ) ( p = 0.29), respectively]. There were no significant between-group differences in occurrence of postreconstruction complications. The authors found significantly higher mean postreconstruction scores in the nipple-sparing mastectomy group within the Satisfaction with Breasts ( p = 0.039) and the Satisfaction with Outcome ( p = 0.017) domains. Finally, they noted higher median postreconstruction scores in the nipple-sparing mastectomy group within the Psychosocial Well-being ( p = 0.043) and Satisfaction with Breasts ( p = 0.004) domains. Conclusions: Psychological concerns regarding malignancy may negatively impact premastectomy patient quality of life. Reconstructive surgery improves patients' postmastectomy quality of life. Nipple-sparing mastectomy appears to provide significantly better improvement in postreconstruction quality of life, specifically in the Satisfaction with Breasts and Satisfaction with Outcome domains of the BREAST-Q, compared with non–nipple-sparing mastectomies. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.